Integrating EFL skills for authentically teaching specific grammar and vocabulary - Julia Sevy-Biloon (Studies in English Language and Education, 2018)
When a person uses a language in an authentic setting, skills such as speaking, reading, writing and listening are naturally integrated to achieve communicative competence. Therefore, this research is based on the use of a content-based instruction model and the communicative language approach to teach English as a foreign language (EFL). The activities described in this article integrate language skills using communicative activities to learn and practice the present perfect and associated new vocabulary. All the skills were evaluated through qualitative informal assessments and quantitative formal testing to see if the chosen strategies could aid in attaining the goals set by the professor and could allow for authentic learning by the participants. This qualitative and quantitative research used 33 sample students, pre- and post-evaluations of all four skills, and questionnaires about the students’ knowledge of the present perfect post-treatment and the opinions of the students about the types of strategies and educational models used to integrate the four language skills in their classes. These results were then used to find out how these teaching strategies could aid in student teaching-learning. The tools used aided in the results were to find out how to integrate communication skills throughout the lessons in the classroom to allow for a more fluid and in-depth learning experience for the intermediate students that participated in this research done at UNAE, Ecuador.